2014
DOI: 10.1111/bcp.12421
|View full text |Cite
|
Sign up to set email alerts
|

Bilastine vs. hydroxyzine: occupation of brain histamine H1‐receptors evaluated by positron emission tomography in healthy volunteers

Abstract: AimA close correlation exists between positron emission tomography (PET)-determined histamine H1-receptor occupancy (H1RO) and the incidence of sedation. Antihistamines with H1RO <20% are classified as non-sedating. The objective was to compare the H1RO of bilastine, a second generation antihistamine, with that of hydroxyzine.MethodsThis randomized, double-blind, crossover study used PET imaging with [11C]-doxepin to evaluate H1RO in 12 healthy males (mean age 26.2 years), after single oral administration of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
31
0
11

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(42 citation statements)
references
References 31 publications
0
31
0
11
Order By: Relevance
“…More recently similar studies have shown bilastine also had a high efflux ratio . The failure of bilastine and fexofenadine to enter the brain and occupy histamine H 1 ‐receptors has been confirmed using positron emission tomography . It is also important to note that total H 1 ‐receptor occupancy (H 1 RO) in the brain for bilastine and fexofenadine was less than zero.…”
Section: Safety Of Bilastinementioning
confidence: 91%
See 1 more Smart Citation
“…More recently similar studies have shown bilastine also had a high efflux ratio . The failure of bilastine and fexofenadine to enter the brain and occupy histamine H 1 ‐receptors has been confirmed using positron emission tomography . It is also important to note that total H 1 ‐receptor occupancy (H 1 RO) in the brain for bilastine and fexofenadine was less than zero.…”
Section: Safety Of Bilastinementioning
confidence: 91%
“…43 The failure of bilastine and fexofenadine to enter the brain and occupy histamine H 1receptors has been confirmed using positron emission tomography. 44,45 It is also important to note that total H 1 -receptor occupancy (H 1 RO) in the brain for bilastine and fexofenadine was less than zero. Thus, these two drugs appear to be truly 'nonsedating' H 1 -antihistamines and the most likely reason for their lack of brain penetration is that they are actively pumped out of the blood-brain barrier by P-gp ( Fig.…”
Section: Safety Of Bilastinementioning
confidence: 99%
“…dose of bilastine 20 mg did not occupy the H 1 -receptors in the brains. 11 Furthermore, bilastine at therapeutic and supratherapeutic doses (20 and 100 mg once daily, respectively) did not induce any clinically significant changes on QT interval corrected for heart rate prolongation in electrocardiogram, 12 and bilastine requires no dose adjustment in patients with renal dysfunction. 13 In randomized double-blind studies in Japan, the efficacy of 2-week treatment with bilastine 20 mg once daily was superior to that of a placebo in Japanese patients with chronic spontaneous urticaria (CSU) 14 or perennial AR.…”
Section: Introductionmentioning
confidence: 87%
“…A clinical pharmacological study using positron emission tomography demonstrated that a single p.o. dose of bilastine 20 mg did not occupy the H 1 ‐receptors in the brains . Furthermore, bilastine at therapeutic and supratherapeutic doses (20 and 100 mg once daily, respectively) did not induce any clinically significant changes on QT interval corrected for heart rate prolongation in electrocardiogram, and bilastine requires no dose adjustment in patients with renal dysfunction …”
Section: Introductionmentioning
confidence: 90%
“…To date, there has been no evidence of sedative or cardiotoxic effects with bilastine in clinical trials or post‐marketing experience . Bilastine's high selectivity for H 1 receptors , limited passage across the blood–brain barrier and negligible metabolism may confer safety and tolerability advantages over other oral second‐generation H 1 antihistamines used to treat these conditions.…”
mentioning
confidence: 99%